2019
DOI: 10.1002/jbt.22426
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐16, as a potential NF‐κB‐related miRNA, exerts anti‐inflammatory effects on LPS‐induced myocarditis via mediating CD40 expression: A preliminary study

Abstract: The purpose of this study was to investigate the biological effect of miR-16 on myocarditis and the underlying molecular mechanism. H9c2 cells were treated with 10 µg/mL lipopolysaccharide (LPS) for 12 hours to form a myocarditis injury model.We observed that LPS treatment distinctly decreased the level of miR-16 in H9c2 cells. Upregulation of miR-16 increased cell proliferation and reduced cell apoptosis.Then, CD40 was predicted and verified as a target gene of miR-16 by TargetScan and luciferase reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…It has been reported that miR-16 can induce the expression of CD40 to play anti-inflammatory role in LPS-induced myocarditis [14]. Consistently, our study showed that miR-16 played inhibitory effects on the apoptosis of cardiomyocyte-induced by LPS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been reported that miR-16 can induce the expression of CD40 to play anti-inflammatory role in LPS-induced myocarditis [14]. Consistently, our study showed that miR-16 played inhibitory effects on the apoptosis of cardiomyocyte-induced by LPS.…”
Section: Discussionsupporting
confidence: 89%
“…It has been well established that many, noncoding RNAs (ncRNAs), such as miRNAs and long ncRNAs (> 200nt, lncRNAs) are involved in LPSmediated inflammation [12], indicating their potential involvement in sepsis. Previous studies have showed that lncRNA CAIF and miR-16 could inhibit LPS-induced inflammatory response [13,14]. This study was therefore carried out to investigate the interactions between CAIF and miR-16 in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“… 59 Besides, miR-16 could mediate the expression of CD40 and inhibit the NF-κB signaling pathway to alleviate LPS-induced myocardial cell injury. 60 Thus, these above-mentioned results should promote further in-depth investigation of HLHS mechanism by which specific miRNAs dysregulate mitochondrial dysfunction via NF-κB signaling.…”
Section: Discussionmentioning
confidence: 94%
“…64 In TB patients, miR-16 is significantly elevated but miR-155 is reduced. 65 While TLR4 stimulation reduces the level of miR-16 that negatively regulates the CD40 expression, 66 Helicobacter pylori infection enhances the expression of miR-155 that promotes CD40 and TNF-a expression. 67 Thus, Mtb infection modulates the expression of miR-16, miR-21, miR-29a, miR-145, miR-146a and miR-155, which in turn regulate CD40 expression ( Figure 3).…”
Section: Mycobacterial Alteration Of Host Micrornamentioning
confidence: 99%